Neck Circumference Is Associated With Hyperuricemia in Women With Polycystic Ovary Syndrome - Yang, Haiyan; Liu, Chang; Jin, Congcong; Yu, Rong; Ding, Lin; Mu, Liangshan (Frontiers in Endocrinology, 2021)
Objective: To evaluate the association between neck circumference (NC) and hyperuricemia in women with polycystic ovary syndrome (PCOS). Methods: This is a cross-sectional study that recruited 601 women with PCOS from January 2018 to January 2021. PCOS was diagnosed according to the Rotterdam definition. Hyperuricemia was defined as serum uric acid level of at least 357 μmol/L. Results: PCOS females with hyperuricemia had significantly greater values of NC, body mass index (BMI), waist circumference (WC) and hip circumference (HC). NC was positively associated with serum uric acid levels, with a standardized regression coefficient of 0.34 after adjusting for confounding factors. Furthermore, logistic regression analysis showed that NC was significantly associated with an increased risk of hyperuricemia, with an adjusted odds ratio of 1.36. The associations between NC and serum uric acid levels were more considerable in those with medium/ high BMI ( BMI ≥ 21.63 kg/m2), all ranges of WC or medium/ high HC (HC ≥ 90 cm). The optimal cut-off point of NC in predicting hyperuricemia was 32.0 cm (Youden index = 0.48), with the sensitivity and negative predictive value of 84.81% and 92.08%, respectively. Conclusions: NC was positively correlated with serum uric acid levels and the prevalence of hyperuricemia in women with PCOS. Therefore, we suggest NC as a simple, novel, and reliable anthropometric measure to be used in the routine clinical assessment of women with PCOS to screen those at high risk of hyperuricemia.